2020
DOI: 10.1109/tip.2020.2999854
|View full text |Cite
|
Sign up to set email alerts
|

OFF-eNET: An Optimally Fused Fully End-to-End Network for Automatic Dense Volumetric 3D Intracranial Blood Vessels Segmentation

Abstract: This is a repository copy of OFF-eNET: An optimally fused fully end-to-end network for automatic dense volumetric 3D intracranial blood vessels segmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Despite the difficulty to segment the vessel tree on CTA data alone, an early feasibility study [Manniesing et al, 2008] has shown a segmentation of the cerebral arterial tree with no additional NCCT is possible. As a successor Nazir et al [2020] proposed a patch-wise segmentation network similar to a ResNet consisting of Inception modules [Szegedy et al, 2015]. In a cross-validation on 70 data sets their approach achieved a Dice score of 89.46%.…”
Section: Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the difficulty to segment the vessel tree on CTA data alone, an early feasibility study [Manniesing et al, 2008] has shown a segmentation of the cerebral arterial tree with no additional NCCT is possible. As a successor Nazir et al [2020] proposed a patch-wise segmentation network similar to a ResNet consisting of Inception modules [Szegedy et al, 2015]. In a cross-validation on 70 data sets their approach achieved a Dice score of 89.46%.…”
Section: Segmentationmentioning
confidence: 99%
“…In a cross-validation on 70 data sets their approach achieved a Dice score of 89.46%. Still, the development of supervised segmentation networks is compounded by the fact that the labeling itself requires an extraordinary effort, as Nazir et al [2020] reported. The labeling of one data set took 6 hours, resulting in roughly a month of work required to annotate 20 cases [Nazir et al, 2020].…”
Section: Segmentationmentioning
confidence: 99%
“…Consequently, local vessels were enhanced and small vessels were better captured. Furthermore, Nazir et al 42 proposed an end‐to‐end Network named OFF‐eNET for automatic segmentation of the volumetric 3D intracranial vascular structures. It enhanced information flow and preserved multiscale features by using up‐skip connections and dilated convolution separately, whereas the up‐skip connections only transferred features locally.…”
Section: Related Workmentioning
confidence: 99%
“…In terms of the segmentation under supervised setting, among the current SOTA methods, the most popular framework is the fully convolutional network (FCN) [35] based encoder-decoder architecture with the representative model like U-Net [45]. So far, to make the conventional encoder-decoder architecture more effective and robust, researchers have made great efforts in the following three directions: 1) developing novel structures, including the 3D structure, recurrent neural network (RNN) based model and cascaded framework [39] [7] [4] [48] [12] [62], 2) designing novel network blocks, including attention mechanism, dense connection, inception or multi-scale fusion [8] [65] [11] [57] [41], and 3) utilizing sophisticated loss functions [58] [10] [26] [61], significantly improving segmentation accuracy.…”
Section: A Medical Image Segmentationmentioning
confidence: 99%